PENERAPAN STRATEGI BERCERITA UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK SISWA KELAS III SD MUHAMADIYAH 6 PEKANBARU - Otang Kurniaman; Muhammad Nailul Huda (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The background of this study is the low listening skills of third-grade students of SD Muhammadiyah 6 Pekanbaru. This research is a classroom action research, which is carried out by applying storytelling strategies. The results of the study stated that the listening skills of students had increased in cycle 1 meeting 1 number of students who scored between 80-100 totaling 12 students, on the internal score 60-79 totaled 3 students, at an interval of 40-59 amounted to 4 students, at intervals of 20 -39 numbered 2 students and in the interval 0-29 there were 0 students. Whereas in cycle 1 meeting 2, the number of students who obtained grades between 80-100 totaled 13 students, in the internal score 60-79 totaled 10 students, at intervals of 40-59 amounted to 0 students, at intervals of 20-39 amounted to 0 students and at interval 0-29 contains 0 students. In cycle 2 meeting 1 listening skills increased the number of students who got grades between 80-100 totaling 15 students, in the internal score 60-79 totaled 8 students, at intervals of 40-59 amounted to 0 students, at intervals of 20-39 amounted to 0 students and in the interval 0-29 there are 0 students. Whereas in the second cycle of meeting 2 the number of students who got a score between 80- 100 totaled 19 students, in the internal score 60-79 totaled 4 students, at intervals of 40-59 amounted to 0 students, at intervals of 20-39 amounted to 0 students and at intervals 0-29 consists of 0 students. Based on these values, it can be concluded that the storytelling strategy can improve the listening skills of third-grade students of SD Muhammadiyah 6 Pekanbaru